EFISIENSI PEMBALAKAN DAN KUALITAS LIMBAH PEMBALAKAN DI HUTAN TROPIKA PEGUNUNGAN: STUDI KASUS DI IUPHHK-HA PT RODA MAS TIMBER KALIMANTAN - Soenarno (BRIN Publishing, 2014)
mprovement of forest management and logging techniques result in increasing of logging efficiency and reducing woodwaste. The research results showed that the average of the logging efficiency in PT Roda Mas Timber Kalimantan is91.41% with various for flat, sloping, rather steep, and steep topographies 90.22%, 91.75%, 90.91% and 90.03%respectively. The average of logging waste is about 1.395 m /tree in which 0.357 m /tree (25,58%) in posses goodquality. The average of logging waste is 1.395 m /tree, which consists of 0.357 m /tree (25.58%) of good quality; 0.610m /tree (43.77%) with natural defect condition, and about 0.428 m /tree (30.65%) of the poor quality.